Curriculum Application: Designing Aims and Learning Outcomes in the English Department - Yulia Agustina; M. Adib Nazri; Hary Murcahyanto (Graduate School of Universitas Negeri Malang, 2023)
The purpose of this study was to determine curriculum developers in determining curriculum objectives, learning outcomes, and aspects of the design of English study programs. This research uses the descriptive qualitative method. Data triangulation, observation, interviews, and documentation were used to collect data using a list of questions related to the curriculum and documentation. The result of this finding is that the English department curriculum is by the applicable standards in Indonesia. In designing the language curriculum, there is only one aspect that has not been applied as an indicator in its design, namely environmental analysis